(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Generation Z, the generation born between 1997 and 2012, is unique and different from previous generations. This generation grew up in the era of digital nativity, and has different characteristics in terms of technology, innovation, entrepreneurship, social sustainability, and environmental, social, and political values. This study aims to determine the influence of entrepreneurial knowledge, personality, and social environment on entrepreneurial interest in generation Z (study on students of the Faculty of Social and Political Sciences, Mulawarman University). The research method used is quantitative which is descriptive. The population in this study is Generation Z who are in the active phase of studying at the Faculty of Social and Political Sciences, while the sample was obtained as many as 100 people. The sampling technique uses non-probability sampling techniques with purposive sampling methods. Data collection in this study used questionnaires made through Google forms. The data was processed using IBM SPSS 26 software with validity test methods and reliability tests, classical assumption tests, multiple linear regression tests and hypothesis tests. The results in this study show (1) Entrepreneur Knowledge has a significant positive effect on Entrepreneurial Interest. (2) Personality has a positive effect but does not have a significant effect on Entrepreneurial Interest. (3) Social Environment has a significant effect on Entrepreneurial Interest.